A canine hybrid double‐bundle model for study of arthroscopic ACL reconstruction. Issue 8 (6th April 2015) - Cook, James L.; Smith, Patrick A.; Stannard, James P.; Pfeiffer, Ferris M.; Kuroki, Keiichi; Bozynski, Chantelle C.; Cook, Cristi R.
ABSTRACT Development and validation of a large animal model for pre‐clinical studies of intra‐articular anterior cruciate ligament (ACL) reconstruction that addresses current limitations is highly desirable. The objective of the present study was to investigate a translational canine model for ACL reconstruction. With institutional approval, adult research hounds underwent arthroscopic debridement of the anteromedial bundle (AMB) of the ACL, and then either received a tendon autograft for "hybrid double‐bundle" ACL reconstruction (n = 12) or no graft to remain ACL/AMB‐deficient (n = 6). Contralateral knees were used as non‐operated controls (n = 18) and matched canine cadaveric knees were used as biomechanical controls (n = 6). Dogs were assessed using functional, diagnostic imaging, gross, biomechanical, and histologic outcome measures required for pre‐clinical animal models. The data suggest that this canine model was able to overcome the major limitations of large animal models used for translational research in ACL reconstruction and closely follow clinical aspects of human ACL reconstruction. The "hybrid double‐bundle" ACL reconstruction allowed for sustained knee function without the development of osteoarthritis and for significantly improved functional, diagnostic imaging, gross, biomechanical, and histologic outcomes in grafted knees compared to ACL/AMB‐deficient knees. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1171–1179, 2015.